In Silico BCell Epitope Design of Zika Virus Vaccine Using â€œZika Virus Isolate Zika Virus/H sapiensTc/Tha/2006/CVD_06020 Complete Genomeâ€ - Savitri, Lisa; Juwita, Syntia Tanu; Antoro, Ester Lianawati; Wulansari, Ida Septika; Sukmawati, Datin An Nisa; Freitas, JoÃ£o GregÃ³rio; Ornai, Andre Mario Sequeira Alves (Biology, Medicine, & Natural Product Chemistry, 2023)
ZIKV has been found in the cerebrospinal fluid (CSF) and brains of adults infected with viruses that manifest neurological disorders. ZIKV is a mosquito-borne single-stranded RNA virus, which belongs to the family Flaviviridae. The efforts of the scientific community have rapidly increased knowledge about this virus. However, understanding the complexities of ZIKV infection, transmission and pathogenesis remains an urgent challenge. Therefore, it is critical to study competent vectors and natural reservoirs for ZIKV, viral genetic diversity and flavivirus coinfection. Due to the great challenges to develop a ZIKV vaccine, it is still not possible to be immunized against ZIKV infection and related pathologies. The methods are nucleotide search for the Zika virus was carried out in silico, using the NCBI bioinformatics application by providing access to biomedical and genomic information. /H. sapiens-tc/THA/2006/CVD_06-020, the complete genome was then searched for FASTA, then prediction of vaccine epitope using the IEDB. The vaccine candidate peptides were analyzed for their antigenicity using VaxiJen. Proteins were classified by AllerTop to known allergenicity, then ToxinPred to predict and design toxic/non-toxic peptides. There are 30 peptide sequences are predicted to be a candidate of peptides B-cell epitope zika virus vaccine design using â€œzika virus isolate zika virus/H. sapiens-tc/THA/2006/CVD_06-020, complete genomeâ€.